2013
DOI: 10.4161/intv.25693
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional microglia response to anti-Aβ treatment in APP/PS1xCX3CR1/GFP mice

Abstract: Senile plaques, mainly composed of amyloid-β (Aβ), are a major hallmark of Alzheimer disease (AD), and immunotherapy is a leading therapeutic approach for Aβ clearance. Although the ultimate mechanisms for Aβ clearance are not well known, characteristic microglia clusters are observed in the surround of senile plaques, and are implicated both in the elimination of Aβ as well as the deleterious inflammatory effects observed in AD patients after active immunization. Therefore, analyzing the direct effect of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…It was also implied that microglia do not successfully clear plaques, unless further activated, suggesting that they restrict senile plaque growth instead, and contribute to the steady state of plaque size after initial formation (Meyer-Luehmann et al, 2008 ). Other studies have shown similar results, and chronic in vivo imaging of microglia clusters did not predict the deposition of new senile plaques (Garcia-Alloza et al, 2013 ), as can be observed in Figure 3 . Comparable observations have also been reported in other AD models (APP/PS1×Iba-1-GFP mice) after long-term in vivo microglia imaging (Bolmont et al, 2008 ).…”
Section: In Vivo Imaging Of Microglia In Alzheimer’s Diseasesupporting
confidence: 73%
See 3 more Smart Citations
“…It was also implied that microglia do not successfully clear plaques, unless further activated, suggesting that they restrict senile plaque growth instead, and contribute to the steady state of plaque size after initial formation (Meyer-Luehmann et al, 2008 ). Other studies have shown similar results, and chronic in vivo imaging of microglia clusters did not predict the deposition of new senile plaques (Garcia-Alloza et al, 2013 ), as can be observed in Figure 3 . Comparable observations have also been reported in other AD models (APP/PS1×Iba-1-GFP mice) after long-term in vivo microglia imaging (Bolmont et al, 2008 ).…”
Section: In Vivo Imaging Of Microglia In Alzheimer’s Diseasesupporting
confidence: 73%
“…It has also been shown that direct administration of anti-Aβ antibodies to APP/PS1/CX3CR1-GFP mice increases microglia size and the number of processes in the close proximity to senile plaques within 1 week. A tendency towards increasing the numbers of cells located in the immediate surround of the senile plaques was also observed (Garcia-Alloza et al, 2013 ). The fact that senile plaques were not cleared in untreated mice, even though extensive microglia numbers were detected around amyloid deposits, supports the idea that mechanisms, both dependent and independent of microglia, may act in the immunotherapy mediated clearance of Aβ plaque (Garcia-Alloza et al, 2013 ).…”
Section: In Vivo Imaging Of Microglia In Alzheimer’s Diseasementioning
confidence: 75%
See 2 more Smart Citations
“…It has been reported that microglia may try to clear A␤ (Morgan, 2006) in order to remove amyloid pathology. As such, microglia seem to play a dual role, and whereas they might control SP deposition, this effect seems to be unsuccessful as the disease progresses and inflammatory deleterious effects, derived from microglia activation, are more prone to appear (Garcia-Alloza et al, 2007;Garcia-Alloza et al, 2013).…”
Section: Discussionmentioning
confidence: 92%